2022
DOI: 10.1039/d2ee01427k
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low voltage bipolar hydrogen production from biomass-derived aldehydes and water in membrane-less electrolyzers

Abstract: Water electrolysis using renewable energy inputs is being actively pursued as a green route for hydrogen production. However, it is limited by the high energy consumption due to the sluggish...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 74 publications
3
52
0
Order By: Relevance
“…Recently, it was demonstrated that electrochemical furfural oxidation competes with the solution phase Cannizzaro reaction, which is the base-mediated disproportionation of aldehydes to their carboxylic acids and alcohols. 39,40 Similarly, we suggest the Cannizzaro reaction as the decisive degradation step for HMF in alkaline media, 41 with further implications for process optimization. The products of this reaction, dihydroxymethylfuran (DHMF) and 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), can be electrooxidized to FDCA as well and allow almost quantitative conversion of the starting HMF.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, it was demonstrated that electrochemical furfural oxidation competes with the solution phase Cannizzaro reaction, which is the base-mediated disproportionation of aldehydes to their carboxylic acids and alcohols. 39,40 Similarly, we suggest the Cannizzaro reaction as the decisive degradation step for HMF in alkaline media, 41 with further implications for process optimization. The products of this reaction, dihydroxymethylfuran (DHMF) and 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), can be electrooxidized to FDCA as well and allow almost quantitative conversion of the starting HMF.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, Liu et al explored the uniqueness of Cu in the electrocatalytic oxidative dehydrogenation (EOD) of aldehydes. 94 They uncovered competing reaction pathways between EOD and non-electrochemical Cannizzaro reaction, which shared a common gem-diol intermediate and exhibited a strong potential dependence. The EOD could involve the adsorption of this diol species on the electrode surface, followed by C–H bond cleavage to produce H 2 .…”
Section: Electrocatalytic Oxidation Of Furansmentioning
confidence: 99%
“…9 However, Pt suffers from severe *CO poisoning given its strong adsorption of *CO (with a binding energy of À1.63 eV, significantly higher than that of *CO on Cu, i.e., À0.63 eV), 9,11 which often leads to a high potential for Pt in order to observe a significant furfural oxidation current (B0.9 V vs. RHE). 9 In this regard, combining Pt and Cu might synergistically enhance the catalytic activity of Cu and the durability of Pt. 12 Given this, we developed a Pt-doped Cu (Pt-Cu) catalyst for furfural oxidation reaction (FOR).…”
Section: R-cho + 2ohmentioning
confidence: 99%
“…Due to the synergistic effect between Pt and Cu, the Pt-Cu catalyst displays an impressive FOR activity with a low potential of only 0.076 V vs. reversible hydrogen electrode (RHE) at 100 mA cm À2 , much superior to the pure Cu catalyst and other recently reported catalysts. [7][8][9][10]13,14 We further designed an acid-alkaline furfural battery that couples alkaline FOR and the acidic hydrogen evolution reaction (HER) to simultaneously generate H 2 from both the anode and cathode, as well as furoate and electricity by effectively utilizing electrochemical neutralization energy (eqn (2), R 0 represents the furan ring), which can provide an extra potential gap of 0.828 V with the consumption of only acid and base (H + + OH À -H 2 O, DG = À79.9 kJ mol À1 ). 15 Notably, the waste acid and base are common in industry and thus can be utilized in this application.…”
Section: R-cho + 2ohmentioning
confidence: 99%
See 1 more Smart Citation